2020
DOI: 10.1200/jco.2020.38.15_suppl.5568
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of germline mutations in African American and Caucasian men with metastatic prostate cancer.

Abstract: 5568 Background: The relevance of germline mutations in metastatic prostate cancer is well established; however, comparison of germline genetics in African American (AA) versus Caucasian (CA) men with metastatic prostate cancer (PCa) is limited. Methods: Germline data from self-identified AA and CA metastatic PCa patients (pts) were collected from 5 academic cancer centers. Various commercial cancer-specific germline testing panels were used to evaluate 12-86 genes. Pathogenic (P) or likely pathogenic (LP) mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…A study of 867 patients with metastatic prostate cancer evaluated the rates of pathogenic variants, likely pathogenic variants, and variants of unknown signficance (VUS) in cancer genes among patients that identified as Caucasian and African American. They showed that the pathogenic and likely pathogenic variants of known cancer genes did not vary by race, however, the rates of VUS were higher in the African American group 57 …”
Section: Novel Genetic Testing Implementation Approachesmentioning
confidence: 99%
“…A study of 867 patients with metastatic prostate cancer evaluated the rates of pathogenic variants, likely pathogenic variants, and variants of unknown signficance (VUS) in cancer genes among patients that identified as Caucasian and African American. They showed that the pathogenic and likely pathogenic variants of known cancer genes did not vary by race, however, the rates of VUS were higher in the African American group 57 …”
Section: Novel Genetic Testing Implementation Approachesmentioning
confidence: 99%
“…Although no differences were noted overall in P/LPV rates between AA and White men, this study also reported lower rates of P/LPVs specifically in non- BRCA genes among AA men than White men. 15 Limitations of this study noted that patients had GT from various laboratories and had a modest sample size. 15 Another study sequenced BRCA1/2 to define the pathogenic spectrum among AA and White men in a cohort of 1,240 patients with PCA, of whom 30% were AA.…”
Section: Introductionmentioning
confidence: 96%
“…14 A multi-institutional study also reported on differences in P/LPVs between AA and White men undergoing GT for PCA. 15 This report included 867 patients, of whom 22% were AA. Although no differences were noted overall in P/LPV rates between AA and White men, this study also reported lower rates of P/LPVs specifically in non- BRCA genes among AA men than White men.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although specific mutations were differentially prevalent between the two groups (MYC amplification, PTEN mutations, and TMPRSS2‐ERG rearrangement), targetable genomic alterations such as the presence of high tumor mutation burden, microsatellite instability, and mutations in DNA damage repair and androgen receptor were not significantly different between the two groups. Although AA men were more likely to harbor germline BRCA alterations, the overall prevalence of germline mutations was similar between AA and White men [14]. With the approval of poly (ADP‐ribose) polymerase (PARP) inhibitors in patients with DNA damage repair mutations [15] and the several molecularly targeted agents in development, these findings suggest the AA men are as likely to harbor these targetable genomic alterations and could benefit from biomarker selected therapy similar to White patients.…”
mentioning
confidence: 99%